(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research has considered the relationship between service quality and customer contentment in e-banking services. The research has considered both the public and private sectors of banks operating in the Delhi region. The research methodology is based on convenience sampling with a sample size of 600 respondents, being customers of banks operating in the selected region within the public and private sectors. The research has considered the main objective to analyse the relationship between the selected service quality dimensions and customer satisfaction in the context of e-banking services. The research has selected various dimensions of service quality based on their relevance and weightage established through customer surveys. The research holds a future significance in the fact that it will help to understand the regional issues of customers and methods to improve service quality accordingly.